Analisis Strategi Penjualan Dalam Meningkatkan Laba Usaha Pada Wisata Buatan di Kota Metro - Ayu Maya Lestari; Dany Arsenio; Fara Khairunnisa; Muhamad Fatikhul Khoir; Carmidah Carmidah (Jurnal Riset Akuntansi, 2024)
This research aims to analyze the marketing strategies implemented by business actors in artificial tourism in Metro City in an effort to increase tourist attraction. The research was conducted through interviews with 15 business actors out of a total of 30 business actors who sell at artificial tourism on Jalan Proklamasi No. 27 Mulyosari. The research results show that business actors implement a pricing strategy based on market prices and provide seating facilities to increase visitor comfort. Several business actors also use social media as a promotional tool. This strategy has proven to be quite effective in maintaining the stability of sales numbers from when it first started operating until 2023. Accordingly, it can be concluded that the combination of competitive pricing, increasing customer comfort, and the use of social media is the right marketing strategy for business actors to implement in artificial tourism in the city. Metro.